Erratum: Magneto‐thermo‐acoustics from magnetic nanoparticles by short bursting or frequency chirped alternating magnetic field: a theoretical feasibility analysis. Med. Phys. 40(6): p. 063301 (2013). Issue 10 (4th August 2019) - Piao, Daqing; Towner, Rheal A.; Smith, Nataliya; Chen, Wei R.
Abstract : We correct one typographical error that has occurred in four equations in Med Phys, 2013. 40(6): p. 063301.